Impact of KIM-1 expression on the advancement of renal failure- A systematic review - Silarapu, Swathi; Jahnavi, Ethakota (International Journal of Psychosocial Rehabilitation, 2020)
One of the major challenges that are being faced by the public healthcare is the renal failure. The suggested ancient clinical biomarkers for this renal failure are the blood urea nitrogen and serum creatinine. But now-a-days these are not considered that sensitive or specific enough as they solely increase significantly after the presence of extensive failure. Therefore there is a need to investigate more of sensitive and specific biomarkers for any type of renal failure is an important factor in nephropathies. Thus specific biomarkers that can help in detecting the injury at the disease starting stage and early diagnosis of these renal diseases would enable better and enhanced therapeutic treatment for the benefit of the individuals in terms of economic and wellbeing. Application of the recent and advanced technologies such as functional genomics, proteomics, and bio fluid profiling has revealed several new molecules that are emerging as predictive biomarkers of renal failure. The most promising and encouraging in current scenario among those include the urinary proteins such as NGAL, KIM-1, and L-FABP (liver-type fatty acid binding protein). Thus keeping all these points in view of the insensitivity and lack of specificity of the traditional and so called gold standard biomarkers the present review focuses on emphasizing the current insights of the novel biomarkers specifically (KIM-1) Kidney Injury Molecule-1. Thus this review gives an insight of the KIM-1 and its expanding evidence as biomarker for early detector in kidney damage and other kidney diseases. It also discusses about the structure, function, detection and signaling pathway.